Carlsbad Current-Argus, December 11, 1961 (Carlsbad Publishing Company, 1961)
Pages from the December 11, 1961 issue of the Carlsbad Current-Argus newspaper with content about Project Gnome. The front page headline reads, "Post-Shot Tests Start at Gnome." There are additional articles about, and images of, the Project Gnome test on subsequent pages. The Atomic Energy Commission detonated a 5-kiloton device underground, 25 miles southeast of Carlsbad, New Mexico. Project Gnome was part of Project Plowshare, the AEC's effort to develop peacetime uses for nuclear explosives.
Keywords: Nuclear energy; Underground nuclear explosions; Nuclear weapons--Testing; U.S. Atomic Energy Commission; Newspapers; New Mexico--Carlsbad; Project Plowshare (U.S.)